2016
DOI: 10.3141/2582-04
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Safety Benefits of the Insurance Corporation of British Columbia Road Improvement Program Using a Full Bayes Approach

Abstract: The objective of this study was to conduct a time-series (before-to-after) evaluation of the safety performance of a sample of locations that have been improved under the Insurance Corporation of British Columbia (ICBC) Road Improvement Program. The program started in 1989 when ICBC established partnerships with local road authorities in British Columbia, Canada, and works cooperatively to make sound investments in road safety improvements. The overall effectiveness of the road improvement program was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Specifically, a comparison group of sites is used for correction of time trend effects, including history and maturation ( 11 ). A reference group is used for correction of the regression to the mean ( 27 ). More details about the EB before–after study can be found elsewhere ( 9, 26 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, a comparison group of sites is used for correction of time trend effects, including history and maturation ( 11 ). A reference group is used for correction of the regression to the mean ( 27 ). More details about the EB before–after study can be found elsewhere ( 9, 26 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, the FB approach efficiently integrates the estimation of the collision prediction model and treatment effects in a single step, leading to a reduction in the data requirement ( 30, 32 ). Thus, advanced evaluation models such as intervention models could be developed with the FB technique ( 27, 28, 31, 34, 35 ).…”
Section: Literature Reviewmentioning
confidence: 99%